2022
DOI: 10.2355/tetsutohagane.tetsu-2022-057
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dislocation Behavior on High Strength and High Ductility of Low Carbon-2%Si-5%Mn Fresh Martensitic Steel

Abstract: Commonly, plain carbon fresh martensitic steel shows high strength and breaking immediately. However, low C-2 wt.%Si-5 wt.%Mn fresh martensitic steel exhibits excellent strength and ductility. But it's not clear why 5 wt.%Mn martensitic steel has ductility more than plain carbon martensitic steel. In this study, the effect of C and Mn on strength and ductility is investigated by in-situ X-ray diffraction during tensile tests in SPring-8. The relationship between the work hardening behavior and the dislocation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Film-like residual austenite can hinder crack propagation and improve toughness [20]. Atsushi Ito et al [21] found that Mn reduces the rate of dislocation multiplication, thereby lowering the work hardening rate. A study by Zhang et al [22] indicated that increasing the oil bath temperature during quenching can increase the amount of retained austenite, and also improve toughness.…”
Section: Introductionmentioning
confidence: 99%
“…Film-like residual austenite can hinder crack propagation and improve toughness [20]. Atsushi Ito et al [21] found that Mn reduces the rate of dislocation multiplication, thereby lowering the work hardening rate. A study by Zhang et al [22] indicated that increasing the oil bath temperature during quenching can increase the amount of retained austenite, and also improve toughness.…”
Section: Introductionmentioning
confidence: 99%